Outcomes of patients with cancer and sarcoid-like granulomatosis associated with immune checkpoint inhibitors: A case–control study. (October 2021) - Cabanié, Charlotte; Ammari, Samy; Hans, Sophie; Pobel, Cedric; Laparra, Ariane; Danlos, Francois-Xavier; Chanson, Noémie; Dolidon, Samuel; Seban, Romain; Voisin, Anne-Laure; Pautier, Patricia; Romano-Martin, Patricia; et al.
Abstract: Purpose: Sarcoid-like granulomatosis (SLG) reaction caused by immunotherapy remains poorly understood. This study aims to investigate the outcome of patients with cancer and SLG associated with immunotherapy. Patients and methods: Between April 2016 and June 2020, 434 patients with immunological adverse events were screened from the ImmunoTOX assessment board of Gustave Roussy, an academic cancer centre in France. Among them, 28 patients had SLG associated with immunotherapy (SLG cohort) and 406 patients had other immunological adverse events (control cohort). Clinical characteristics and outcome of patients were compared from SLG and control cohort. Results: The SLG cohort consisted of 28 patients, 14 women and 14 men, with the median (range) age of 56.5 (28.7–75.3) years. Patients in the SLG cohort with sarcoidosis were asymptomatic (only radiographical finding) in 13 (46.4%) cases; otherwise, the most frequent symptoms were dyspnoea in 8 (28.6%) patients and cough in 5 (17.8%) patients. The computerised tomography scan found sarcoidosis localisations in mediastinal or peri-hilar thoracic lymph nodes in 26 (92.9%) patients, and lung parenchymal involvement was found in 14 (50.0%) patients. The radiographic Scadding stages for sarcoidosis classification were distributed in stages 0, I, II, III and IV in 2 patients (7.1%), 13 patients (46.4%), 11 patients (39.3%), 1 patient (3.6%) and 1 patient (3.6%), respectively. Compared with patients with other immunological toxicities (cohort control), patients with sarcoidosis presented most frequently with melanoma (75.0% versus 21.9% of patients; p < 0.001) and more often received combined therapies of anti–programmed cell death 1 plus anti–cytotoxic T-lymphocyte antigen 4 protein (46.4% versus 12.6% of patients; p = 0.002). Patients with sarcoidosis had an improved overall survival (OS); the median OS was not reached in the SLG cohort and 40.4 months in the control cohort, hazard ratio = 0.232 (95% confidence interval: 0.086–0.630) (p = 0.002). Conclusion: Sarcoidosis-like reactions in patients receiving immunotherapy were reported as non-severe immunological reactions in most cases and were correlated with improved OS. SLG should not be misdiagnosed as tumour progression in patients receiving immunotherapy treatment for cancer. Highlights: Sarcoidosis associated with immunotherapy correlated with improved overall survival. Sarcoidosis associated with anticancer immunotherapy was generally of mild severity. Sarcoidosis seems more related to the combination of anti–programmed cell death 1 plus anti–cytotoxic T-lymphocyte antigen 4 protein.